Effects of the characteristics of online multimedia synergy on consumers' message acceptance and message response. Issue 5 (11th September 2017) - Dong, Xuebing; Chang, Yaping; Fan, Xiaojun
Abstract : Purpose: Marketers recognize that the internet is crucial in the lives of consumers; thus, they invest money on online advertisements. Using multiple online media primarily influences the message acceptance of consumers. The synergistic effect of online multimedia relies on form, content, and sources of information, and time. The paper aims to discuss these issues. Design/methodology/approach: A model that reflects the influence of the characteristics of online multimedia on message response through message acceptance is established based on theories of information persuasion, encoding variability, and multiple-source assumption. Based on a survey of 411 online media users, the study applies partial least-squares regression to test the research model. Findings: The results show that variety of forms, complementary of contents, diversity of sources, and time interval influence message response via message strength. Complementary of contents and diversity of sources affect message response via perceived credibility. Synergy type moderates the relationship between variety of forms and perceived credibility and between diversity of sources and perceived credibility. Research limitations/implications: The current study mainly tests the effect of these characteristics on message response and the moderating effect of synergy type. Future research can examine the effect of these characteristics on information seeking and consumption behavior and the moderating effect of the cognitive mode of consumers. Practical implications: This study provides insight into the characteristics of synergy and contributes to the literature on integrated marketing communication. The results provide guidance for practitioners to effectively plan online multimedia practices. Originality/value: This study explored the influence of the characteristics of online media synergy on message response through message acceptance. The study also discussed the moderating effect of the type of online multimedia synergy.